TENSIONS IN PEDAGOGICAL COMPETENCE OF ELEMENTARY MADRASAH TEACHERS IN IMPLEMENTING DIFFERENTIATED LEARNING - Hasan Al Banna; Vina Febiani Musyadad; Rendi Atnanto; Muhammad Reza Pahlevi; Mia Audina Musyadad (Jurnal Ilmiah Pendidikan Dasar (JIPDAS), 2026)
Transformation of learning in elementary education requires teachers to accommodate diverse student characteristics through a differentiated approach. In Madrasah Ibtidaiyah (Islamic elementary school), this demand overlaps with the responsibility to strengthen Islamic values, giving rise to unique dynamics in pedagogical practice. This study aims to analyze the tensions between teachers' pedagogical competencies in implementing differentiated learning at Madrasah Ibtidaiyah Al-Umm Klari. The study employed a qualitative case study approach. Data were collected through participant observation, in-depth interviews, and documentation studies, then analyzed interactively through reduction, presentation, and drawing conclusions. The results indicate that differentiation has been attempted through a variety of tasks and learning products, but has not been consistently integrated into the process and assessment aspects. School policy support is normative, while technical implementation relies on teacher initiative. Tensions arise from administrative burdens, time constraints, and classroom management challenges in managing diverse activities. These findings confirm that the implementation of differentiation is not only related to teachers' conceptual understanding but also to the readiness of the school system. The implications of this research emphasize the importance of strengthening operational guidelines, ongoing training, and professional collaboration to support a more adaptive learning transformation in madrasahs.